Relugolix for oral treatment of uterine leiomyomas: a dose-finding, randomized, controlled trial - Hiroshi Hoshiai; Yoshifumi Seki; Takeru Kusumoto; Kentarou Kudou; Masataka Tanimoto (BMC, 2021)
Abstract Background Uterine leiomyomas are the most common neoplasm affecting women and frequently cause heavy menstrual bleeding and pain. Gonadotropin-releasing hormone (GnRH) receptor antagonists provide fast symptom relief and show promise as a medical (non-surgical) treatment option and as a presurgical treatment to reduce leiomyoma size. The aim of this study was to evaluate the efficacy and safety of three dose levels of oral relugolix, a small molecule GnRH receptor antagonist, in Japanese women with uterine leiomyomas and heavy menstrual bleeding. Methods This phase 2, multicenter, double-blind, parallel-group study was conducted at 36 sites in Japan in women with uterine leiomyomas and heavy menstrual bleeding, defined as a pictorial blood loss assessment chart (PBAC) score of ≥ 120 in one menstrual cycle. Patients were randomized 1:1:1:1 to relugolix 10, 20, or 40 mg, or placebo, orally once daily for 12 weeks. The primary endpoint was the proportion of patients with a total PBAC score of < 10 from week 6 to 12. A sample size of 50 patients per group was estimated to provide ≥ 95% power, based on the comparison of relugolix 40 mg with placebo using a chi-square test with a significance level of 5% (two-sided). Results From November 2011 to September 2012, 216 patients were randomized and 214 patients (99.1%) were analyzed. The proportion (difference vs. placebo) of patients that achieved the primary endpoint in the placebo and 10-, 20-, and 40-mg relugolix groups were 0%, 20.8% (95% confidence interval [CI]: 9.3-32.3, P < .001), 42.6% (95% CI: 29.4-55.8, P < .001), and 83.3% (95% CI: 73.4-93.3, P < .001), respectively. Though treatment-emergent adverse events were similar between the 20- and 40-mg groups, the incidence rates were more frequent compared with the placebo group. Most of these adverse events were mild or moderate in intensity. Conclusions Relugolix decreased menstrual blood loss in women with uterine leiomyomas in a dose-response manner, and was generally well tolerated. Clinical trial registration: ClinicalTrials.gov, https://clinicaltrials.gov/ct2/show/NCT01452659 , NCT01452659 (registered 17/10/2011); JAPIC Clinical Trial Information, https://www.clinicaltrials.jp , JapicCTI-111590 (registered 31/08/2011).